2021
DOI: 10.3389/fmicb.2021.610437
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome Intermediate Accumulation During in situ Nitrate Remediation in Groundwater by Hydrogenotrophic Denitrification

Abstract: Bioremediation of polluted groundwater is one of the most difficult actions in environmental science. Nonetheless, the clean-up of nitrate polluted groundwater may become increasingly important as nitrate concentrations frequently exceed the EU drinking water limit of 50 mg L–1, largely due to intensification of agriculture and food production. Denitrifiers are natural catalysts that can reduce increasing nitrogen loading of aquatic ecosystems. Porous aquifers with high nitrate loading are largely electron don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…accumulation [40]. Combining biological denitrification with ironbased abiotic nitrite reduction (the addition of Fe(II)-containing minerals) was also suggested to counteract nitrite accumulation and foster complete hydrogenotrophic denitrification [41].…”
Section: Discussionmentioning
confidence: 99%
“…accumulation [40]. Combining biological denitrification with ironbased abiotic nitrite reduction (the addition of Fe(II)-containing minerals) was also suggested to counteract nitrite accumulation and foster complete hydrogenotrophic denitrification [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies within the Nueces Estuary have found SGD contributions to be significant (Douglas et al, 2020;Murgulet et al, 2022), with important fluxes of nutrients and DOM that could impact ecosystem health (Douglas et al, 2021a;Douglas et al, 2021b). Though groundwater is generally rich in NO 3 − (Kennedy et al, 2009;Duffner et al, 2021), transport from aquifers to estuaries facilitates conversion to, and accumulation of, NH 4 + in saline and anoxic porewaters (Santos et al, 2009;Lopez et al, 2020;Wong et al, 2020;Douglas et al, 2021b). From the long-term analyses, surface water NH 4 + is negatively correlated with water level (p-value = 0.03) and positively with creek discharge (p-value = 0.02).…”
Section: Hydrologic Changes and Relationships To Nutrient Supplymentioning
confidence: 98%
“…Nocadia was defined as hydrogen-oxidizing bacteria, and is able to utilize H 2 as the electron donor and O 2 as the electron accepter [27]. Pseudomonas and Thermonas were known as typical active denitrifiers when organic carbon was available; however, these genera were suggested in the main hydrogenotrophic denitrifiers community [28]. Hydrogenophaga was commonly found in the denitrification system, and, after carrying out hydrogenotrophic denitrification, was higher in the BER-10 (2.7%) than that in the BER-20 (1.9%).…”
Section: Bacterial Community Of Bersmentioning
confidence: 99%